PENYAKIT AKAR GANODERMA PADA SENGON DI SLEMAN, YOGYAKARTA - Tri Maryono (Jurnal Pemuliaan Tanaman Hutan, 2020)
Ganoderma root disease in the community forest of sengon is one of the limiting factor to increase the productivity of sengon wood. This disease has been reported in West Java, East Java, South Sumatra and South Kalimantan. The survey was conducted to determine the existence of Ganoderma root disease in three sengon fields in Sleman, Yogyakarta. The existence of Ganoderma root disease was recognized based on the symptoms of diseased plants and the present of Ganoderma basidiocarp on the diseased sengon stem. The survey results on three sengon fields was succeed in finding diseased plants and also the basidiocarp of Ganoderma on the basal of the diseased plant stem. Symptoms that have been found was either dead or dying trees (few leaves left). The basidiocarp of Ganoderma on the diseased plants varies in characteristic while its young and mature. The basidiospores is ellipsoid, truncate, rough (coarsely echinulated), and double-walled. The Ganoderma colony was white and turned to yellow orange from the center. Based on this study the Ganoderma root disease in sengon plants has developed in Sleman, Yogyakarta. The presence of dead or dying trees with few leaves left between healthy sengon trees and the presence of Ganoderma basidiocarp in diseased trees are indicator of the presence of root disease in the sengon field caused by Ganoderma.